Mountains as sacred spaces - Berner, Ulrich (Culture and religion, 2020)
Sacred mountains are well known from all over the world, especially as places for pilgrimage. Classical phenomenology of religion used to present them as places of a hierophany and/or as spaces for a numinous experience. Although both these concepts – ’hierophany’ and ’numinous experience’ – have been the target of severe criticism in Religious Studies, it may be rewarding to redefine them as purely descriptive categories and discuss the applicability to various kinds of mountain-experiences: from religious pilgrimage in Late Antiquity as, for instance, climbing Mount Sinai, to extreme-sports in modern times as, for instance, free-soloing in the Yosemite National Park.